Levocardia With Situs Inversus Atria (Case Report) - Bambang Madiyono; Irawati Pulungan; P. M. C. Pelupessy; Maemunah Affandi (Paediatrica Indonesiana, 1976)
Three cases of Levocardia and situs inversus atria were reported. The clinical diagnosis of the first two cases were based on clinical signs and laboratory findings which were confirmed by Electrocardiography, Chest Xray, heart catheterization and angiography. The third case died before further investigations could be done. Classification, management and prognosis were also discussed.